Mapping of Global Publications on Artificial Intelligence: A Scientometric Analysis - Togam, Madhukar; Naikar, Satishkumar; Krishnamurthy, C; Hatti, Shashikumar (Bibliotecas. Anales de investigación, 2025)
Objective: Artificial Intelligence (AI) has emerged as an innovative technology with the potential to revolutionize various industries. This study uses a scientometric methodology to evaluate the current research in artificial intelligence comprehensively. Design/Methodology/Approach: This study employed scientometric indicators to identify key trends, patterns, and research gaps in the existing literature. A comprehensive dataset of 1803 academic papers on artificial intelligence, published between 2003 and 2023, was assembled and assessed using the Scopus database. Various scientometric instruments, such as Biblioshiny and VOSviewer, have significantly improved this study. Results/Discussion: The study’s results provide substantial insights. The research indicated that the peak number of publications occurred in 2021, totaling 601 (33.33%), with the predominant document type being articles at 771 (42.76%), succeeded by conference articles at 428 (23.74%). Journal articles demonstrated the highest prevalence among various publication categories, comprising 771 (42.76%), followed by conference papers at 428. The United States emerged as the foremost contributor with 405 articles, followed by India with 234 publications. Conclusions: The University of Birmingham emerged as the most distinguished affiliation, boasting 17 publications and 1,670 citations. The "Lecture Notes in Computer Science (including the subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)" series is the most productive source, releasing 100 papers, of which 97 were cited. The author, Liu Xiaoxuan, is a distinguished figure with an h-index of 13 and a g-index of 14. Contribution: To assess the state of AI scientific production in the period 2021-2023, to contribute to scientific research.